Réponses

2013-05-01T20:32:12+02:00

A = (x+3)(a+5)

A = xa +5x +3a +15

 

 

B= (a +6)(5+b)

B = 5a +ab +30 +6b

 

C = (x+2)(y-1)

C= xy -x +2y -2

 

D = (a-2)(b+4)

D = ab +4a -2b -8

2013-05-01T20:32:32+02:00

Bonsoir,

 

On applique la formule :

\left(a+b\right)\left(c+d\right) = ac+ad+bc+bd

 

a)\left(x+3\right)\left(a+5\right)\\ =ax+5x+3a+3\times 5\\ =ax+5x+3a+15\\

 

b)\left(a+6\right)\left(5+b\right)\\ =5a+ab+6\times 5+6b\\ =5a+ab+6b+30

 

c)\left(x+2\right)\left(y-1\right)\\ =xy-x+2y-2

 

d)\left(a-2\right)\left(b+4\right) = ab+4a-2b-8